FKBP12 Depletion Leads to Loss of Sarcoplasmic Reticulum Ca2+ Stores in Rat Vas Deferens - Christianne B.V. Scaramello; Humberto Muzi-Filho; Gisele Zapata-Sudo; Roberto T. Sudo; Valéria do M.N. Cunha (Journal of Pharmacological Sciences, 2009)
The immunophilin 12-kDa FK506 binding protein (FKBP12) stabilizes intracellular Ca2+ release channel (CRC) activity in different tissues. In this work, the presence of FKBP12 in rat vas deferens (RVD) and its possible contribution to RVD function was investigated. Treatment under appropriate pH, temperature, and ionic conditions was used to strip FKBP12 from CRC binding sites; Western blotting revealed FKBP12 in control but not in treated homogenates. Disruption of the FKBP12-CRC complex in RVD decreased the Ca2+ content of sarcoplasmic reticulum (SR) by increasing Ca2+ leakage through the ryanodine receptor (RyR3 isoform) but not through 1,4,5-iNOSitol trisphosphate receptors (IP3R1 and IP3R3 isoforms). The decrease of SR Ca2+ content was not related to inhibition of SERCA ATPase. It seems that dissociation of FKBP12-RyR leads to conformational changes in RyR that make it difficult for ryanodine to access its binding site. Rapamycin, which is commonly used as a pharmacological tool to disrupt the FKBP12-RyR complex, decreased phenylephrine-induced contractions in RVD epididymal halves. The data suggest that FKBP12 is expressed in RVD in a labile association with RyR3. Disruption of the FKBP12-RyR3 complex may lead to modifications of RVD physiology and in consequence may compromise male fertility. Keywords:: calcium, 12-kDa FK506 binding protein (FKBP12), ryanodine receptor, SERCA, rat vas deferens